Formation of extraordinarily high waves in space and time - Clauss, Günther F.; Klein, Marco; Onorato, Miguel (Volume 2: Structures, Safety and Reliability, 2011)
The existence of freak waves is indisputable due to observations, registrations, and severe accidents. The occurrence of extreme waves, their characteristics and their impact on offshore structures is one of the main topics of the ocean engineering research community. Real sea measurements play a major role for the complete understanding of this phenomenon. In the majority of cases only single point registrations of real sea measurements are available which hinders to draw conclusions on the formation process and spatial development in front of and behind the respective registration points. One famous freak wave is the "New Year Wave", recorded in the North Sea at the Draupner jacket platform on January 1st, 1995. This wave has been reproduced in a large wave tank and measured at different locations, in a range from 2163 m (full scale) ahead of to 1470 m behind the target position - 520 registrations altogether. Former investigations of the test results reveal freak waves occurring at three different positions in the wave tank and these extreme waves are developing mainly from a wave group. The possible physical mechanisms of the sudden occurrence of exceptionally high waves have already been identified - superposition of (nonlinear) component waves and/or modulation instability (wave-current interaction can be excluded in the wave tank). This paper presents experimental and numerical investigations on the formation process of extraordinarily high waves. The objective is to gain a deeper understanding on the formation process of freak waves in intermediate water depth such as at the location of the Draupner jacket platform where the "New Year Wave" occurred. The paper deals with the propagation of large amplitude breathers. It is shown that the mechanism of modulation instability also leads to extraordinarily high waves in limited water depth. Thereby different carrier wave length and steepnesses are systematically investigated to obtain conclusions on the influence of the water depth on the modulation ...